Edukasi Perilaku Sehat Dalam Menjaga Kesehatan Organ Reproduksi Pada Remaja Putri Di Sekolah Dasar Mis Al-Kautsar Tahun 2025 - Rani Cahya; Sah Marianta Ginting; Melisa Anggryani Sitorus; Debora Keresya Pane; Hikmah Mia Syahira (STIKES Columbia Asia Medan, 2025)
Adolescent reproductive health is a crucial issue often overlooked in primary education, especially for young girls. The lack of accurate and age-appropriate information causes confusion among students when experiencing puberty, including menarche. This community service project aims to increase the knowledge and awareness of female students at MIS AL-KAUTSAR regarding reproductive organ health through an educational and participatory approach. The method used is Participatory Action Research (PAR), consisting of needs identification, program planning, educational implementation, and evaluation stages. The results indicate a significant increase in students' understanding of reproductive anatomy and hygiene, as well as behavioral changes such as greater openness to discussing menstruation and the emergence of local leaders among students. The program also led to the creation of new social structures in the school, such as a youth information corner and the involvement of female teachers as mentors. This initiative proves effective as an educational intervention model that can be replicated in other primary schools.